2021
DOI: 10.1152/japplphysiol.00090.2021
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of muscle Igf1 exacerbates disuse atrophy weakness in mice

Abstract: Muscle atrophy occurs as a result of prolonged periods of reduced mechanical stimulation associated with injury or disease. The growth hormone/insulin-like growth factor-1 (GH/IGF-1) axis and load sensing pathways can both aid in recovery from disuse through their shared downstream signaling, but their relative contributions to these processes are not fully understood. The goal of this study was to determine if reduced muscle IGF-1 altered the response to disuse and reloading. Adult male mice with inducible mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The loss of muscle strength was greatest in Igf1-deleted mice following disuse. The return of muscle mass and strength in recovery seemed independent of Igf1 concluding Igf1 as one of the key players in muscle degradation (Spradlin et al, 2021). Vogel et al…”
Section: Ogneva Et Al Reported On Multiple Generations Of Drosophilamentioning
confidence: 97%
See 1 more Smart Citation
“…The loss of muscle strength was greatest in Igf1-deleted mice following disuse. The return of muscle mass and strength in recovery seemed independent of Igf1 concluding Igf1 as one of the key players in muscle degradation (Spradlin et al, 2021). Vogel et al…”
Section: Ogneva Et Al Reported On Multiple Generations Of Drosophilamentioning
confidence: 97%
“…The loss of muscle strength was greatest in Igf1 ‐deleted mice following disuse. The return of muscle mass and strength in recovery seemed independent of Igf1 concluding Igf1 as one of the key players in muscle degradation (Spradlin et al, 2021 ). Vogel et al reports on human cells (Jurkat T‐cells, U937) that were exposed to altered gravity within short duration gravitational transitions in parabolic flight (Vogel et al, 2019 ).…”
Section: Alteration Of Circadian Clock and Spaceflight: An (Anti)agin...mentioning
confidence: 99%
“…In addition, adiponectin plays the role of anti-inflammatory by inhibiting TNFa, improving liver steatosis and inflammation (102,103). Fat accumulation and aging damage the signaling pathway of the GH/ IGF-1 axis, leading to decreased levels of muscle synthesis (104, 105). In an animal model, NAFLD is reported to be associated with decreased muscle mass and strength as well as decreased IGF-1 levels, suggesting that decreased IGF-1 may contribute to the development of NAFLD-related sarcopenia (106).…”
Section: Sarcopenia and Cytokine Disordersmentioning
confidence: 99%
“…Hambretch et al (2005) [ 8 ] observed that exercise increases muscle IGF-1, whereas they did not find changes in other tissues. Moreover, it has been demonstrated that muscle IGF-1 deletion induces muscle weakness and atrophy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%